1986
DOI: 10.1111/j.1651-2227.1986.tb10155.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow in Preterm Infants during the First Week of Life

Abstract: Forty-two preterm infants of 28-33 weeks of gestation were studied once during the first week of life by 133-Xenon clearance after intravenous injection to estimate global cerebral blood flow. Count rates detected over the chest were corrected for chest wall contribution and used as arterial input function. A neonatal blood-brain partition coefficient of Xenon was used for the calculation of a mean flow estimator (CBF-infinity). The technique was internally validated by use of differently obtained arterial inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
61
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(73 citation statements)
references
References 29 publications
11
61
0
1
Order By: Relevance
“…Values for CBF and COD were comparable to those previously obtained by NIRS and other techniques (20,21). Because no effect of giving surfactant on these variables could be detected, these results do not suggest that this treatment causes persistent cerebral ischemia, although they do not exclude transient effects.…”
Section: >S Et Alsupporting
confidence: 74%
See 1 more Smart Citation
“…Values for CBF and COD were comparable to those previously obtained by NIRS and other techniques (20,21). Because no effect of giving surfactant on these variables could be detected, these results do not suggest that this treatment causes persistent cerebral ischemia, although they do not exclude transient effects.…”
Section: >S Et Alsupporting
confidence: 74%
“…The effects of this therapy on infants immediately after surfactant by a median of -0. 21 intracerebral complications, such as PVH, that lead to later (range -0.46 to 0.05) m L 100 g-I, but quickly recovered morbidity are less certain. Most randomized trials show no so that the median change during the 10 min after surfac-evidence of a change in the incidence of PVH in infants treated tant was 0.01 (-0.46 to 0.46) mL.lOO g-I.…”
mentioning
confidence: 99%
“…The finding of extremely low WM flows is consistent with measurements of mean global CBF in ventilated human premature infants (13)(14)(15)(16)(17)(18)(19). The studies of regional CBF by positron emission tomography showed that values in cerebral WM in surviving preterm infants with normal or near normal neurologic outcome ranged from only 1.6 to 3.0 mL·100 g Ϫ1 ·min Ϫ1 (12).…”
supporting
confidence: 77%
“…Xenon clearance, by using inhaled xenon gas, is another technique that is closely related to SPECT and has been extensively used in adults and neonates. 30 Patient motion is a serious limitation of the technique, which, moreover, does not cover the whole brain. The mean CBF with the xenon technique has been estimated at around 50 mL/100 g/min in 7 healthy neonates 31 and 9.5-11.7 mL/100 g/min in 22 preterm infants during the first 3 days of life.…”
mentioning
confidence: 99%